2011 Triennial Surveillance Review : Review of the 2007 Surveillance Decision and the Broader Legal Framework for Surveillance. (Policy Papers; Policy Paper ;, 2011)
This paper reviews the 2007 Surveillance Decision and the broader legal framework for surveillance. While the 2007 Surveillance Decision on Bilateral Surveillance over Members' Policies (thereafter, the 2007 Decision) requires the Fund to review the decision itself, this paper takes a broader view. It recognizes that the 2007 Decision cannot be assessed in isolation from the legal framework it derives from, id est, the Articles of Agreement, and that a debate on the adequacy of this broader framework is also necessary. The paper therefore discusses the strengths and limitations of the current system as set out in both the Articles of Agreement (primarily, Article IV) and the 2007 Decision and explores options going forward.